ADVANCING EXCHANGES OF INFORMATION IN SOCIAL FRIENDSHIP NETWORKS THROUGH MOTIVATION, OPPORTUNITY, AND ABILITY - Anandya, Dudi; Pawitra, Teddy; Balqiah, Tengku E. (Universitas Brawijaya, Indonesia, 2018)
This article examines the impact of motivation, opportunity, and ability as antecedents of exchanges of information among members of social friendship networks and also the impact on creating membership value and members'loyalty including the influence of the system characteristics. The research method employed descriptive multiple crosssectional designs which yielded 256 responses. The Structured Equation Modelling was used to test the hypotheses. The findings of the research reveal that motivation and ability provide the impetus to exchanges of information whereas opportunity does not. Furthermore, exchanges of information impact members' loyalty through the mediation of membership value and finally the exchanges of information evoke members'loyalty directly. However, only information quality impacts membership value and members'loyalty. The rigor of the research concept will result in better insight to future researchers particularly in designing and implementing members'loyalty program in social friendship networks.